(untitled) (CAHIERS MAGELLANES-NS, 2024)
Physical test models and techniques tailored to the characteristics of children and sports are essential in identifying children’s talents. Purpose: This study analyzed the need for a physical test instrument consisting of bio-motor strength, flexibility, and balance. Another purpose was to analyze the need for a technical test instrument consisting of 7 basic aerobic gymnastic steps in the national development category. Design/methodology/approach: This descriptive quantitative study utilized a questionnaire as its research instrument, with the study sample involving 25 students. The data were analyzed using the calculation of percentage statistical data.Result: The study results show that the flexibility test model obtained a dominant value of 44% (included in the easy category), the balance test model obtained a dominant value of 36% (included in the very easy category), and the strength test model obtained a dominant value of 40% (include in the fairly easy category). As for the results of technical abilities, namely: the results of the march technique (88%), jogging technique (60%), jumping jack (92%), and lunges (40%) fell under the very easy category. Meanwhile, skip technique (40%), knee lift (40%), and high kick (56%) are included in the quite easy category.Conclusion: (1) physical and technical test instruments can be used to identify children’s talents in the national development category of aerobic gymnastics, and (2) physical and technical test instruments developed by the researchers are acceptable, appropriate, useful, and can be implemented by children in the national development category of aerobic gymnastics.